Gender and Family in Modern Acehnese Society - Kiram, Muhammad Zawil (Sociology Department Of Syiah Kuala University, 2020)
Since it was declared as one of the crucial issues in the Sustainable Development Goals agenda by the United Nations, gender equality has entered every country including in the Acehnese family. As a province that implements Islamic law and rich in local wisdom, Aceh has its own perspective in responding to the issue of gender equality. Although in the past (in terms of religion and culture) Aceh recognized the existence of the same position between men and women in the family, in its implementation gender equality has not achieved completely. The cultural shift and understanding of Acehnese society towards gender, which is considered as an ideology from the West, has become one of the big walls in the realization of gender equality in the family. The culture of the society that stigmatizes men as weak people if they are involved in domestic affairs also plays a major role. In addition, the most influential thing is the absence of gender-based education both in families and social institutions in Acehnese society, therefore the generation that grows continues to develop with the same understanding as their predecessors which resulted in the discourse of gender equality in modern Aceh society being a mere delusion.